2017
DOI: 10.1080/17482631.2017.1379338
|View full text |Cite|
|
Sign up to set email alerts
|

“Football is a boys’ game”: children’s perceptions about barriers for physical activity during recess time

Abstract: The aim of the study was to know the factors that influence boys and girls’ perceptions for performing physical activity during playground recess from their own perspective. Ninety-eight schoolchildren aged 8–11 years from five schools from Cuenca (Spain) participated in 22 focus groups and carried out 98 drawings following the socioecological model as a theoretical framework. A content analysis of the transcripts from the focus groups and drawings was carried out by three researchers. Results showed that, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 42 publications
(76 reference statements)
1
42
0
1
Order By: Relevance
“…These results are similar to those found in other studies that analyzed children's sports preferences [16,45,46] and seem to remain true throughout life [47]. Sports segregation according to gender roles may be related to the fear of being judged or bullied if gender norms are not conformed to [37,48]. In fact, various articles have shown that girls are more likely to engage in team sports when other girls are playing but not when boys are playing, because boys may exclude girls when they try to participate in sports in which girls are not socially considered good enough [49][50][51].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are similar to those found in other studies that analyzed children's sports preferences [16,45,46] and seem to remain true throughout life [47]. Sports segregation according to gender roles may be related to the fear of being judged or bullied if gender norms are not conformed to [37,48]. In fact, various articles have shown that girls are more likely to engage in team sports when other girls are playing but not when boys are playing, because boys may exclude girls when they try to participate in sports in which girls are not socially considered good enough [49][50][51].…”
Section: Discussionsupporting
confidence: 89%
“…In our results, a higher and more intense physical activity practice by boys than by girls was appreciable, being higher their PAL (1.46 ± 0.07 vs. 1.44 ± 0.07; p < 0.001) the time spent in MVPA (0.90 ± 0.45 h/day vs. 0.74 ± 0.40 h/day; p < 0.001) ( Table 2) and their adherence to physical activity recommendations (42.0% vs. 23.46%; p = 0.000),as it occurred in other studies with schoolchildren population, such as the ANIBES study in Spain [33], the Youth Study in China [34] or the study of Williamson et al performed in England and Scotland [35]. A possible explanation to this situation is that during school breaks or after-school day care, boys usually take advantage of this time to practice sports, while girls use this time in sedentary activities focused on socialization [36][37][38]. This is reflected, too, in the differences found among sexes when time dedicated to active play was analyzed, as boys spent more time on active play than girls (p = 0.014), which is partly attributable to the poor distribution of space in school playgrounds or sports facilities, as it does not take into account different sporting preferences, to the prejudice of those children who do not use material like football goal posts or basketball nets, who are generally girls [37,39].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, it was found that boys and girls did not participate in the same activities, however, girls who wished to be part of boys' games had their skills tested to be accepted. 17 An expressive number of reports highlighted the cries expressed by athletes, both in situations of defeat, due to dissatisfaction with the result, and in victories for the emotion generated by the conquest.…”
Section: Discussionmentioning
confidence: 99%
“…Those girls and boys, who did not play football were dis-placed to peripheral areas and the lack of materials was a barrier for them. Likewise, the teachers themselves were a barrier for all children who did not play football (Martínez, Gutiérrez, Rodríguez, Pardo, & Martínez, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%